Wind pressure measurements on a vaulted canopy roof. Issue 223 (April 2022) - Pagnini, Luisa; Torre, Stefano; Freda, Andrea; Piccardo, Giuseppe
Abstract: A vaulted free-standing canopy roof to be built in a University Campus is investigated by wind tunnel experiments to address the lack of information for this structural shape. First set of tests investigates the model in isolated configuration; second set reproduces the nearby buildings as well as the topography of the surroundings; third set is carried out sealing the building envelope. Mean and peak pressure coefficients are then estimated over the outer and inner surface, also supplying the net values. At the best knowledge of the authors, there are only two well documented experiments on this topic, without information available about peak values. Comparison of results obtained in the different configurations as well as with other wind tunnel tests on vaulted canopies underlines the importance of reproducing the correct geometry of the structure and its details, such as eaves and skylight, for the reliable definition of wind loads, in addition to nearby buildings and surroundings when the canopy is placed in its real position. Finally, a proposal for wind pressure zoning is provided, which can be useful to define design criteria as well as for regulatory use. Highlights: Wind tunnel tests have been carried out on a vaulted canopy roof. Mean and peak pressure coefficients have been obtained on the outer and inner surface. Results in different configurations underline the importance of reproducing details. Results are compared with available mean pressure coefficients. Proposal for design is provided by the method of zoning for wind pressure.